Eufemisme dalam wacana lingkungan sebagai piranti manifestasi manipulasi realitas: perspektif ekolinguistik kritis - Elisa Nurul Laili (Jurnal Linguistik Terapan, 2016)
Nowadays, the language studies also uncover the language usage packaged in the diction and new terms created by the journalists in environmental discourses. For the certain reason, often journalists create and use the language features such as figure of speeches and language style. Euphemism is one of figure of speeches that often found in Indonesian mass media. Not only for language politization device, the use of euphemism on environmental discourse in Indonesian mass media is reflected in the use of new terms that often concealing the true facts about environment. Euphemism in environmental discourse is more various than in sociolinguistic scope, which often have the close relationship with taboo concept. Euphemism in environmental discourse not only replacing the taboo terms, but has more politically and ideologically usage. This paper will discuss about the use of euphemism in environmental discourse by the ecocritical discourse analysis perspective.